Pengaruh Nutrisi Terhadap Jumlah Bakteri Indigenous pada Limbah Tahu: The Effect of Nutrition on the Number of Bacteria in Tofu Waste - Tridesianti, Siska; Darniwa, Adisty Virakawugi; Suryani, Yani; Novianti, Devi; Aji, Luthfi Akmal; Adisty Virakawugi Darniwa, Adisty Virakawugi Darniwa; Yani Suryani, Yani Suryani; Devi Novianti, Devi Novianti; Luthfi Akmal Aji, Luthfi Akmal Aji (Jurnal Sumberdaya Hayati, 2025)
Indigenous bacteria found in natural environments, such as tofu waste, are strongly influenced by environmental factors and environmental nutrients. The purpose of this study was to determine the effect of tofu waste nutrients on the number of indigenous bacteria in tofu waste. The parameters observed were the characteristics of tofu waste, such as color, aroma, acidity level (pH), and analysis of nutrient content through proximate tests, as well as the calculation of the number of indigenous bacteria using the Total Plate Count method. The results showed that tofu waste was yellowish in color and had a soy aroma, but there was a slight sour aroma in tofu liquid waste. Tofu solid waste had a pH of 6, while tofu liquid waste had a pH of 5. The levels of nutrients, namely protein, fat, ash, and carbohydrates, were higher in tofu solid waste, while the water content was higher in tofu liquid waste. The total indigenous bacteria in tofu solid waste were higher (3.78 × 106 CFU/mL) than in tofu liquid waste (5.55 × 105 CFU/mL). This study concluded that high nutrient content correlated with an increase in the number of indigenous bacteria in tofu waste.